2017
DOI: 10.1158/1078-0432.ccr-15-2388
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc Modulation and Acetylation Is a Key HDAC Inhibitor Target in Cancer

Abstract: Purpose: Histone deacetylase inhibitors (HDACi) are promising anticancer drugs. Although some HDACi have entered the clinic, the mechanism(s) underlying their tumor selectivity are poorly understood. Experimental Design and Results: Using gene expression analysis, we define a core set of six genes commonly regulated in acute myeloid leukemia (AML) blasts and cell lines. MYC, the most prominently modulated, is preferentially altered in leukemia. Upon HDACi treatment, c-Myc is acetylated at lysine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 54 publications
3
93
1
Order By: Relevance
“…However, the level of c‐Myc binding to E2F1 promoters was not increased when transfected with plasmids encoding c‐Myc (K323Q) that imitated the acetylation status of c‐Myc (data not shown). It was reported that K323 overacetylation might cause reduced c‐Myc protein stability while preserving stability in normal conditions . This observation may explain why c‐Myc was not always highly expressed in E7‐expressing cells .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the level of c‐Myc binding to E2F1 promoters was not increased when transfected with plasmids encoding c‐Myc (K323Q) that imitated the acetylation status of c‐Myc (data not shown). It was reported that K323 overacetylation might cause reduced c‐Myc protein stability while preserving stability in normal conditions . This observation may explain why c‐Myc was not always highly expressed in E7‐expressing cells .…”
Section: Resultsmentioning
confidence: 99%
“…Acetylation of c‐Myc by CBP and GCN5/PCAF prevents its degradation and stimulation of c‐Myc transcriptional activity . However, another study found that c‐Myc overacetylation at K323 may reduce its stability . c‐Myc plays a critical role for transformation of human cells by HPV E6 and E7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both HDAC inhibition and FL AR depletion by 2‐75 could contribute to the observed c‐Myc downregulation. Inhibition/abrogation of c‐Myc is a key event of HDAC inhibition . Various mechanisms, for example, targeting class 1/class 2 (eg, HDAC7) HDACs to suppress MYC transcription or induction of c‐Myc‐targeting microRNA to inhibit protein translation, etc., have been shown to result in persistent down‐modulation of c‐Myc in different cancer phenotypes.…”
Section: Discussionmentioning
confidence: 99%